A detection system with broad angular acceptance for particle identification and angular distribution measurements - Carnelli, Patricio Francisco Florencio; Arazi, Andrés; Fernández Niello, Jorge Oscar; Capurro, Oscar Ángel; Cardona, Maria Angélica; de Barbará, Ezequiel; Figueira, Juan Manuel; Hojman, Daniel Leonardo; Martí, Guillermo Virginio; Martinez Heimann, Diego; Negri, Agustin Eduardo; Pacheco, Alberto Jorge (Elsevier Science, 2013)
Fil: Carnelli, Patricio Francisco Florencio. Comisión Nacional de Energía Atómica. Gerencia del Area de Investigación y Aplicaciones No Nucleares. Gerencia Física. (Centro Atómico Constituyentes) Proyecto Tandar; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de San Martin; Argentina